Arranjos supramoleculares de triazenidos complexos de Ag(I) através de ligações de hidrogênio - Locatelli, Aline (2008)
In this work we synthesized and determinates the crystaline/molecular structure of thre Ag(I) complexes, all of them use monocatenated triazenide ligands previously desprotonated. The complex [Ag(C6H4FNNNC6H4NO2)(C5H5N)]2 (1) crystallizes in triclinic system, space grup P1¯ with cell parameters = 9,6008(3), b = 12,1025(4), c = 16,4071(5) Å, α= 104,035(2)°, β= 105,209(2)°, γ = 103,897(2)°; V = 1688,13(9) Å; Z = 2. The refinement of this structure converge to the follow discordance indexes R₁ = 0,0624 e wR₂ = 0,0870. The sphere of coordination around the Ag atom is formed by two deprotonated triazene ligants and molecules of pyridine. The Ag Ag interaction expands the coordination geometry of Ag of T distorted for trigonal bipyramidal distorted. The molecules of complex (1) binding by non-classic hydrogen bonds intermolecular C(52)-H(52) O(22) [3,158(8) Å; 127°] e C(62)-H(62)···(O11) [3,156(8) Å; 128°] play a role in the formation of supramolecular arrangement. The complex [Ag(C6H4ClNNNC6H4NO2)(C5H5N)]2 (2) crystallizes in triclinic system, space grup P1¯ with cell parameters a = 7,4042(10), b = 11,3767(2), c = 12,1174(4) Å, α= 113,356(10)°, β= 97,402(10)°, γ = 101,498(2)°; V = 893,42(4) Å; Z = 1. The refinement of this structure converge to the follow discordance indexes R1 = 0,0271 e wR2 = 0,0782. The sphere of coordination around the Ag atom is formed by two deprotonated triazene ligants and molecules of pyridine. The Ag Ag interaction expands the coordination geometry of Ag of T distorted for trigonal bipyramidal distorted. The molecules of complex (2) binding by non-classic hydrogen bonds intramolecular C(32)-H(32) O(11) [3,500(3) Å; 170°] and binding by non-classic hydrogen bonds intermolecular C(33)-H(33) (O12) [3,376(4) Å; 152°] play a role in the formation of supramolecular arrangement. The complex [Ag(C6H4BrNNNC6H4NO2)(C5H5N)]2 (3) crystallizes in triclinic system, space grup P1¯ with cell parameters a = 7,502(10), b = 11,483(2), c = 12,060(4) Å, α= 113,42(10)°, β= 96,71(10)°, γ = 102,49(2)°; V = 906,60(4) Å; Z = 1. The refinement of this structure converge to the follow discordance indexes R1 = 0,0323 e wR2 = 0,0500. The sphere of coordination around the Ag atom is formed by two deprotonated triazene ligants and molecules of pyridine. The Ag Ag interaction expands the coordination geometry of Ag of T distorted for trigonal bipyramidal distorted . The molecules of complex (3) binding by non-classic hydrogen bonds intramolecular C(32)-H(32) O(11) [3,487(4) Å; 170°] and binding by non-classic hydrogen bonds intermolecular C(33)-H(33) (O12) [3,380(4) Å; 151°] play a role in the formation of supramolecular arrangement.